DOPPLER UMBILICAL FLOW WAVEFORMS IN MILD HYPERTENSIVE PREGNANCY - Maysoon Sharief (The Medical Journal of Basrah University, 2007)
ABSTRACT Objective: To assess the relationship between the Doppler umbilical artery flow velocity waveforms (AB ratio) in mild hypertensive pregnancy and the fetal outcome. Materials & Methods: This is prospective study which carried out between January 2004 and January 2005. Doppler examination of the umbilical artery was available for 135 pregnant women within 1 week of delivery. The value of the last Doppler AB ratio was classified into 3 groups: normal (AB ratio is <95th centile value) high AB ratio (if AB ratio is >95th but <99th centile value) and extreme AB ratio (if ratio is >99th centile value). Results: Normal AB ratio was found in 91% of mild hypertensive women and 82% of cases were delivered after 36 weeks with average mean birth weight and good Apgar score (more than 6 at one minute). Abnormal ratio was found in 5% of mild hypertensive cases with 40% of them was delivered before 36 weeks with significant admission in the intensive baby care unit. Conclusion: Doppler study can be used as a good tool for assessment of high risk fetus in mild hypertensive women.